Hypoxia-Induced miR-378a-3p Inhibits Osteosarcoma Invasion and Epithelial-to-Mesenchymal Transition via BYSL Regulation - Zhang, Junlei; Tang, Haijun; Jiang, Xiaohong; Huang, Nenggan; Wei, Qingjun (Frontiers in Genetics, 2022)
The bystin-like (BYSL) gene is expressed in a wide range of eukaryotes and is closely associated with tumor progression. However, its function and mechanism in osteosarcoma remain unclear. Herein, the protein expression and clinical role of BYSL in human osteosarcoma tissues were assessed. High expression of BYSL was positively related to the metastasis status and poor patient prognosis. Mechanistically, upregulation of BYSL enhanced Nrf2 expression under hypoxia. MicroRNAs are important epigenetic regulators of osteosarcoma development. Noteworthy, bioinformatics analysis and dual-luciferase reporter and rescue assays showed that miR-378a-3p inhibited BYSL expression by binding to its 3ʹ-untranslated region. Analysis of miR-378a-3p function under hypoxia and normoxia showed that its upregulation suppressed osteosarcoma tumor invasion and inhibited epithelial-to-mesenchymal transition by suppressing BYSL. Collectively, the results show that the miR-378a-3p/BYSL axis holds potential for predicting metastasis risk in osteosarcoma.